Chemopreventive effect of chalcone derivative, L2H17, in colon cancer development. Issue 1 (December 2015) - Xu, Shanmei; Chen, Minxiao; Chen, Wenbo; Hui, Junguo; Ji, Jiansong; Hu, Shuping; Zhou, Jianmin; Wang, Yi; Liang, Guang
Abstract Background Colon cancer is the third most commonly diagnosed cancer and the second leading cause of cancer mortality worldwide. Chalcone and its derivatives are reported to exhibit anti-cancer effects in several cancer cell lines, including colon cancer cells. In addition, chalcones have advantages such as poor interaction with DNA and low risk of mutagenesity. In our previous study, a group of chalcone derivatives were synthesized and exhibited strong anti-inflammatory activities. In this study, we evaluated the anti-cancer effects of the chalcone derivative, L2H17, in colon cancer cells. Methods The cytotoxicities of L2H17 on various colon cancer cell lines were investigated by MTT and clonogenic assay. Cell cycle and apoptosis analysis were performed to evaluate the molecular mechanism of L2H17-mediated inhibition of tumor growth. Also, scratch wound and matrigel invasion experiments were performed to estimate the cell migration and invasion after L2H17 treatment. Finally, we observed the anti-colon cancer effects of L2H17 in vivo. Results Our data show that compound L2H17 exhibited selective cytotoxic effect on colon cancer cells, via inducing G0/G1 cell cycle arrest and apoptosis in CT26.WT cells. Furthermore, L2H17 treatment decreased cell migration and invasion of CT26.WT cells. In addition, L2H17 possessed marked anti-tumor activity in vivo. The molecular mechanism of L2H17-mediated inhibition of tumor promotion and progression were function through inactivated NF-κB and Akt signaling pathways. Conclusions All these findings show that L2H17 might be a potential growth inhibitory chalcones derivative for colon cancer cells.